2018
DOI: 10.1002/pds.4401
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the impact of pharmacoepidemiologic research using altmetrics: A case study of aCNODESdrug‐safety article

Abstract: Compared with traditional citation-based metrics, altmetrics take a more holistic view of research impact, attempting to capture the activity and engagement of both scholarly and nonscholarly communities. Despite the limited theoretical underpinnings, possible commercial influence, potential for gaming and manipulation, and numerous data quality-related issues, altmetrics are promising as a supplement to more traditional citation-based metrics because they can ingest and process a larger set of data points rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…4 A recent study concerning pharmacoepidemiologic research concluded that altmetrics confer a more comprehensive evaluation of research impact, as they are able to incorporate the activity and engagement of scholarly and nonacademic communities alike. 10 Future research will need to focus on better delineating the impact of altmetrics in the age of growing social media, as it appears that altmetrics may have a large role in disseminating publications regarding the orthopaedic surgery literature.…”
Section: Discussionmentioning
confidence: 99%
“…4 A recent study concerning pharmacoepidemiologic research concluded that altmetrics confer a more comprehensive evaluation of research impact, as they are able to incorporate the activity and engagement of scholarly and nonacademic communities alike. 10 Future research will need to focus on better delineating the impact of altmetrics in the age of growing social media, as it appears that altmetrics may have a large role in disseminating publications regarding the orthopaedic surgery literature.…”
Section: Discussionmentioning
confidence: 99%
“…Extending this study to social media coverage would be a valuable addition; there are large and meaningful discussion sections accompanying some of the articles in this study (eg, doc09). Our research group has studied the altmetrics of our research on social media [81]. Combining these two research arms in a single stream could provide more nuanced results.…”
Section: Future Studymentioning
confidence: 99%
“…In this paper wider interest in scientific outputs is measured by altmetric indicators. We are aware that altmetric data are not standardized, that impact may be manipulated due to gaming (Gamble et al, 2017), that it lacks an integrative theory and may not reflect scientific impact (Williams, 2017;Roemer and Borchardt, 2015). However, altmetric interest in Biomedical and Life sciences is likely to be high (Fang et al, 2020) and use of Internet and related social media can be intensified for the acquisition of information during health emergency (An et al, 2018).…”
Section: Rapid Response To Covid-19 In Latin Americamentioning
confidence: 99%